2020
DOI: 10.1177/1947603520941239
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Molecular Biomarkers for Use in Human Knee Osteoarthritis: A Systematic Review

Abstract: Objective Biomarkers in osteoarthritis (OA) could serve as objective clinical indicators for various disease parameters, and act as surrogate endpoints in clinical trials for disease-modifying drugs. The aim of this systematic review was to produce a comprehensive list of candidate molecular biomarkers for knee OA after the 2013 ESCEO review and discern whether any have been studied in sufficient detail for use in clinical settings. Design MEDLINE and Embase databases were searched between August 2013 and May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 81 publications
0
18
0
1
Order By: Relevance
“…Despite a huge ongoing effort in the detection of blood-based diagnostic markers, no single blood biomarker has emerged so far, however. 6 Previous studies have suggested a potential role of fatty acid–binding protein 4 (FABP4), oxidized low-density lipoprotein (oxLDL), membrane-bound phospholipase A2 (PLA2G2A) and soluble receptor for advanced glycation end-products (sRAGE) in the pathogenesis of osteoarthritis (OA). 7-10 Cytoplasmic FABP4, a member of the FABP superfamily and mostly expressed in adipocytes, regulates intracellular fatty acid transportation by increasing fatty acid solubility and facilitating transport to cellular compartments and specific enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a huge ongoing effort in the detection of blood-based diagnostic markers, no single blood biomarker has emerged so far, however. 6 Previous studies have suggested a potential role of fatty acid–binding protein 4 (FABP4), oxidized low-density lipoprotein (oxLDL), membrane-bound phospholipase A2 (PLA2G2A) and soluble receptor for advanced glycation end-products (sRAGE) in the pathogenesis of osteoarthritis (OA). 7-10 Cytoplasmic FABP4, a member of the FABP superfamily and mostly expressed in adipocytes, regulates intracellular fatty acid transportation by increasing fatty acid solubility and facilitating transport to cellular compartments and specific enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bone and cartilage metabolism biomarkers such as Vitamin D, CTX-II, PINP [ 31 ], MMP3, and COMP [ 32 ], along with lipid markers such as adiponectin [ 33 ], leptin [ 34 ], resistin, and visfatin [ 35 ], were analyzed in both groups. Among all the biomarkers studied, there was a significant increase in the MMP3 level and decreased vitamin D levels in OA rats compared to the sham group at 12 weeks postOA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the lack of a significant difference between the OA and sham-OP rats, regarding the transforming growth factor-beta 1 (TGf-β1) and C-reactive protein levels, indicated that our OA induction on the single joint did not involve systemic inflammation. Furthermore, bone and cartilage metabolism biomarkers such as Vitamin D, CTX-II, PINP [31], MMP3, and COMP [32], along with lipid markers such as adiponectin [33], leptin [34], resistin, and visfatin [35], were analyzed in both groups. Among all the biomarkers studied, there was a significant increase in the MMP3 level and decreased vitamin D levels in OA rats compared to the sham group at 12 weeks postOA.…”
Section: Serum Level Oa Biomarkers' Detection and Evaluationmentioning
confidence: 99%
“…As the most widely studied and applied biomarker in clinical practice, calprotectin is known to be a promising noninvasive biomarker of inflammatory bowel disease (IBD). 16-18 Fecal calprotectin is reported to be strongly associated with disease activity indices and endoscopic activity in IBD. 16 Recently, serum calprotectin has also attracted attention as a novel blood-based biomarker of IBD, which correlates with endoscopic findings of the patients.…”
Section: Discussionmentioning
confidence: 99%